ChemInform Abstract: Recent Developments in Chemistry and Biology of Curcumin Analogues. Issue 34 (26th August 2014) - Bairwa, Khemraj; Grover, Jagdeep; Kania, Mihir; Jachak, Sanjay M.
Abstract Review: 113 refs.